Using binocular pupillometry method for evaluating the functional state of persons - Matveev, I. A.; Varchenko, N. N.; Gankin, K. A. (Sports Technology, 2015)
The method of binocular pupillometry is presented with an application to evaluate the functional state of athletes. The method is based on registration of pupil reaction to a light flash stimulus. The reaction reflects the state of sympathetic-parasympathetic balance of autonomic nervous system and serves as an objective measurement of the body condition. Synchronous binocular registration of pupillograms allows to reveal the asymmetry of the neural system, which manifests hemisphere dominance and provides individual psychic characteristics. Results of the experiments performed with various groups of athletes and control group of non-sportive persons are presented. Comparison with traditional methods of functional state evaluation is done.